Pemahaman Remaja Pengguna Alat Ortodontik Dalam Perawatan Kesehatan Gigi Dan Mulut - Ardian Priyambodo; Ira Liasari; Jumriani; Zahra Nurfadilah Rahmat (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2026)
Oral and dental health is an essential component of overall health, playing a significant role in mastication, speech, and facial aesthetics. Maintaining oral hygiene is particularly important for orthodontic patients, as fixed appliances may increase the risk of plaque accumulation and oral health problems. This study aimed to determine the level of understanding of orthodontic appliance users regarding dental and oral health care among adolescent patients. This research employed a descriptive qualitative approach involving 30 adolescents aged 10–24 years a private clinic in Makassar, selected using purposive sampling. Data were collected through an online questionnaire with open-ended questions and analyzed using coding and thematic analysis. The results showed that most respondents had a good understanding of the risks associated with orthodontic treatment, including dental caries, gingivitis, calculus formation, and halitosis. Respondents also demonstrated appropriate oral hygiene behaviors, such as regular tooth brushing, use of additional cleaning aids (dental floss, interdental brush, mouthwash, and water flosser), and routine dental check-ups. However, several challenges were identified, including mechanical difficulties in cleaning teeth, discomfort or pain, and psychosocial barriers. Overall, the high level of understanding was influenced by effective education and communication provided by dental health professionals. It can be concluded that adolescents using orthodontic appliances have a high level of understanding, which contributes to better oral health care practices.